Emerging digital technologies and India's security sector : AI, blockchain, and quantum communications - Jha, Pankaj; Polcumpally, Arun Teja; Saigal, Vedant (London : Routledge, 2024)
This book is an introductory account for policy makers, academia, and interested readers on the digital technologies on Indian Military. It covers three technologies - AI, Blockchain, and Quantum communications - and provides a detailed account on the military use cases. It evaluates the readiness of Indian Military in these technologies. A foundational text, it not only provides key policy analysis but also identifies the gray areas for the future research in the security studies. The volume will be essential reading for scholars and researchers of military and strategic studies, especially future warfare, AI and Blockchain, and South Asian studies. It will be of interest to general readers as well.
Introduction Arun Teja PolcumpallyPART I 1 Frontier Technologies Will Enhance the Power of the State Arun Teja Polcumpally2 War, Hybrid War, and Revolution in the Military Arun Teja Polcumpally3 Quest for Military Supremacy: the United States vs. China vs. Russia Poornima Vijaya4 Non-Traditional Security + Data: The Road Not Taken Arun Teja PolcumpallyPART II 5 Artifi cial Intelligence and Its Probable Military Disruptions Vedant Saigal6 Quantum Communications in Indian Armed Forces Rushil Khosla7 Application of Blockchain Technology in Military Affairs Sonchita Debnath8 Cyber Security Structure in India Vedant Saigal and Arun Teja Polcumpally9 Is India Ready With the Digital Army? Arun Teja PolcumpallyConclusion Pankaj K Jha
Keywords: National security -- Technological innovations -- India; Artificial intelligence -- Military applications -- India; Blockchains (Databases) -- India; Quantum communication -- India; COMPUTERS / Artificial Intelligence; POLITICAL SCIENCE / Political Freedom & Security / International Security